Cutis verticis gyrata: a cutaneous finding in acromegaly - Giullia Menuci Chianca Landenberger; Bárbara Roberta Ongaratti; Júlia Fernanda Semmelmann Pereira-Lima; Miriam da Costa Oliveira (Sociedade Brasileira de Dermatologia, 2022)
Abstract Acromegaly is a rare disease characterized by changes in the bone and soft tissue systems, induced by excess growth hormone and insulin-like growth factor type 1. Among the skin lesions associated with acromegaly is cutis verticis gyrata, an hypertrophic, and coarse folding of the skin of the scalp, an association of uncommon incidence and unknown prevalence. This case report describes the case of a patient diagnosed with acromegaly at age 60 with previously unidentified cutis verticis gyrata. This report aims to review the literature on cutis verticis gyrata and its unusual association with acromegaly.